2021
DOI: 10.1093/cid/ciab367
|View full text |Cite
|
Sign up to set email alerts
|

Comparative 1-Year Outcomes of Invasive Staphylococcus aureus Infections Among Persons With and Without Drug Use: An Observational Cohort Study

Abstract: Background Persons who use drugs (PWUD) face substantial risk of Staphylococcus aureus infections. Limited data exist describing clinical and substance use characteristics of PWUD with invasive S. aureus infections or comparing treatment and mortality outcomes in PWUD vs. non-PWUD. These are needed to inform optimal care for this marginalized population. Methods We identified adults hospitalized from 2013-2018 at 2 medical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, in a previous study, 70% of patients with SUDs were found to complete Staphylococcus aureus bacteremia treatment, which is similar to the treatment completion in our cohort without a conference. 32 Of patients who had an OPTIONS-DC, 83.6% completed treatment. We hypothesize that OPTIONS-DC may increase the likelihood of long-term antibiotic treatment completion in patients with SUDs and would be important to evaluate in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…However, in a previous study, 70% of patients with SUDs were found to complete Staphylococcus aureus bacteremia treatment, which is similar to the treatment completion in our cohort without a conference. 32 Of patients who had an OPTIONS-DC, 83.6% completed treatment. We hypothesize that OPTIONS-DC may increase the likelihood of long-term antibiotic treatment completion in patients with SUDs and would be important to evaluate in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…A Danish study by Thønnings et al [24] found that hospitalized PWID had an overall bacteremia rate of 22% with S. aureus being the most common pathogen. In a retrospective cohort study Appa et al [25] comparing S. aureus invasive infections in PWID with non-PWID, they found a significantly higher rate of endocarditis, deep-seated infections, vertebral osteomyelitis and MRSA in the PWID group. Furthermore, they found that a significant lower number of PWID completed their antibiotic treatment and a higher readmittance rate with S. aureus infection 1 year following discharge.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no formal comparison group in this small pilot study, we note that in a previously published cohort study of a similar population not receiving CM, antibiotic completion for PWUD with serious bacterial infections was 69% and 25% self-directed their discharge. 1 Moreover, IMPACT participants described that this intervention was effective in encouraging antibiotic completion, citing satisfaction with the visits breaking up the long acute care stay, developing a trusting relationship, and the financial incentives.…”
Section: Discussionmentioning
confidence: 99%
“…S uccessful treatment of serious infections among people who use drugs (PWUD) remains challenging given undertreated substance use disorders (SUD), stigma, competing life priorities, and more limited discharge options after hospitalization compared with non-PWUD. [1][2][3] Contingency management (CM), a behavioral treatment anchored in operant conditioning that involves frequent assessment of objective behavior change with paired incentives, is an underused strategy that has proven efficacious in addressing SUD and separately infection treatment adherence. Numerous randomized trials have supported CM efficacy in treating methamphetamine use disorder, cocaine use disorder, and opioid use disorder, with additional studies demonstrating CM efficacy in HIV, hepatitis C, and tuberculosis treatment.…”
mentioning
confidence: 99%